2008
DOI: 10.1016/j.anbehav.2008.06.001
|View full text |Cite
|
Sign up to set email alerts
|

What's in a peck? Using fixed action pattern morphology to identify the motivational basis of abnormal feather-pecking behaviour

Abstract: Like many captive animals, hens, Gallus gallus, used for agricultural production perform abnormal behaviours. They are particularly prone to feather pecking, the severest form of which involves the pecking at and removal of feathers, which can cause bleeding and even stimulate cannibalism. The two main hypothesized explanations for feather pecking concern frustrated motivations to forage or, alternatively, to dustbathe, leading to redirected behaviour in the form of pecks at plumage. Previous work on pigeons h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 40 publications
1
44
0
2
Order By: Relevance
“…The blood corticosterone, glucose and triglycerides were lower than respective levels in controls. Olsson & Keeling (2005) and Dixon et al (2008) found that the behaviour of taking dust baths is an important indicator of social welfare of birds. According to Sherwin & Kelland (1998), the higher welfare in turkeys increased the time spent in stretching, feather pecking, and dust bathing.…”
Section: Discussionmentioning
confidence: 99%
“…The blood corticosterone, glucose and triglycerides were lower than respective levels in controls. Olsson & Keeling (2005) and Dixon et al (2008) found that the behaviour of taking dust baths is an important indicator of social welfare of birds. According to Sherwin & Kelland (1998), the higher welfare in turkeys increased the time spent in stretching, feather pecking, and dust bathing.…”
Section: Discussionmentioning
confidence: 99%
“…DIXON et al (2008) noted that the behavior of feather pecking of severe way is associated to motivational frustrations about scratching, and not about the dustbath, as reported by SHIELDS et al (2004), because the morphology of feather pecking is closer to foraging, unlike the morphology of taking a dustbath and of cleaning the feathers.…”
Section: Resultsmentioning
confidence: 74%
“…GRAVES (1982) stated that behavior is a window of the body for the outside, enabling better estimate with precision the welfare of birds. OLSSON et al (2005) and DIXON et al (2008) found that the behavior of taking the dust bath is an important indicator of social welfare of the group, and this behavior is mainly affected by the bedding material (JONG et al, 2007). ZIMMERMAN et al (2006) observed that different sizes of groups provide significant differences in the expressions of aggressive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…De Haas et al (2010) deduced that high featherpecking birds have a stronger pecking motivation than low feather-pecking birds, rather than a preference for eating feathers. Newberry et al (2007) also found that birds which performed more SFP performed more ground-pecking during rearing, and Dixon et al (2008) deduced that birds with a high foraging motivation can be more likely to perform SFP if foraging behaviour is inhibited. Kjaer (2009) suggested a hyperactivity model for SFP, whereby birds that perform more SFP have higher general activity levels.…”
Section: Discussionmentioning
confidence: 96%